Changes in cognitive functioning after COVID-19: A systematic review and meta-analysis - Crivelli, Lucía (2022)
Introduction: We conducted a systematic review and meta-analysis of the cognitive effects of coronavirus disease 2019 (COVID-19) in adults with no prior history of cognitive impairment. Methods: Searches in Medline/Web of Science/Embase from January 1, 2020, to December 13, 2021, were performed following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A meta-analysis of the Montreal Cognitive Assessment (MoCA) total score comparing recovered COVID-19 and healthy controls was performed. Results: Oof 6202 articles, 27 studies with 2049 individuals were included (mean age = 56.05 years, evaluation time ranged from the acute phase to 7 months post-infection). Impairment in executive functions, attention, and memory were found in post-COVID-19 patients. The meta-analysis was performed with a subgroup of 290 individuals and showed a difference in MoCA score between post-COVID-19 patients versus controls (mean difference = −0.94, 95% confidence interval [CI] −1.59, −0.29; P =.0049). Discussion: Patients recovered from COVID-19 have lower general cognition compared to healthy controls up to 7 months post-infection.